A Comparison of the Long-Term Surgical Outcomes of Horizontal Strabismus Surgery between Resident Clinic and Private Clinic Patients. (18th August 2022) - Dakroub, Mohamad; El Hadi, Dalia; Hashim, Ibrahim; El Moussawi, Zeinab; Ibrahim, Perla; Al-Haddad, Christiane
ABSTRACT: Purpose: To compare the long-term surgical outcomes of patients with horizontal strabismus whose surgery was performed in an outpatient department (OPD) setting (by residents-in-training) to those whose surgery was performed in a private clinic (PC) setting (by staff-ophthalmologists) in the same operating room/institution. Methods: Two hundred and forty-four patients' charts who had horizontal strabismus surgeries from January 2007 to 2020 were reviewed retrospectively. A total of 92 patients were operated on by residents and followed in OPD, and 152 patients by staff-surgeons and followed in PC. Demographic data and eye exam parameters were collected. Distance and near deviation (in prism diopters, PD) were extracted and compared between groups at baseline and postoperatively (6 months and yearly for up to 6 years). Success was defined as a postoperative motor alignment of 10PD or less. Results: The mean age of the 244 patients was 10.5 ± 11.7 years, with no significant differences between groups. A longer follow-up duration was reported in the PC group (34.9 ± 24.3 months vs 25.3 ± 20.2 months). Patients had similar success rates in both groups in the early postoperative period (6 months and 1 year); however, a higher success rate was observed in the PC group compared to OPD at 3, 5 and 6 years with the following respective values: 72.2% vs 50% (p < .001), 75% vs. 66.7% (p = .02), and 68.6% vs. 66.7% (p = .03). The difference was more pronounced in the esotropia subgroup mostly at 3 years follow-up. Conclusion: This study showed a similar success rate of horizontal strabismus surgery performed in a PC setting by staff surgeons as compared to that performed in an OPD setting by residents at 6 months and 1 year. A significantly higher success rate was observed at long term follow-up (after 2 years) in the PC group compared to the OPD group, possibly related to the difference in compliance with post-operative follow-up management and not to surgery itself.